Chromosomal islands of Streptococcus pyogenes and related streptococci: molecular switches for survival and virulence - Nguyen, Scott V.; McShan, William M. (Frontiers in Cellular and Infection Microbiology, 2014)
Streptococcus pyogenes is a significant pathogen of humans, annually causing over 700,000,000 infections and 500,000 deaths. Virulence in S. pyogenes is closely linked to mobile genetic elements like phages and chromosomal islands (CI). S. pyogenes phage-like chromosomal islands (SpyCI) confer a complex mutator phenotype on their host. SpyCI integrate into the 5’ end of DNA mismatch repair (MMR) gene mutL, which also disrupts downstream operon genes lmrP, ruvA, and tag. During early logarithmic growth, SpyCI excise from the bacterial chromosome and replicate as episomes, relieving the mutator phenotype. As growth slows and the cells enter stationary phase, SpyCI reintegrate into the chromosome, again silencing the MMR operon. This system creates a unique growth-dependent and reversible mutator phenotype. Additional CI using the identical attachment site in mutL have been identified in related species, including Streptococcus dysgalactiae subsp. equisimilis, Streptococcus anginosus, Streptococcus intermedius, Streptococcus parauberis, and Streptococcus canis. These CI have small genomes, which range from 13-20 kB, conserved integrase and DNA replication genes, and no identifiable genes encoding capsid proteins. SpyCI may employ a helper phage for packaging and dissemination in a fashion similar to the Staphylococcus aureus pathogenicity islands (SaPI). Outside of the core replication and integration genes, SpyCI and related CI show considerable diversity with the presence of many indels that may contribute to the host cell phenotype or fitness. SpyCI are a subset of a larger family of streptococcal CI who potentially regulate the expression of other host genes. The biological and phylogenetic analysis of streptococcal chromosomal islands provides important clues as to how these chromosomal islands help S. pyogenes and other streptococcal species persist in human populations in spite of antibiotic therapy and immune challenges.